Hubungan Paparan Pestisida Dengan Kandungan Arsen (As) Dalam Urin dan Kejadian Anemia (Studi : Pada Petani Penyemprot Pestisida di Kabupaten Brebes) - Elanda Fikri; Onny Setiani; Nurjazuli Nurjazuli (Master Program of Environmental Health, Faculty of Public Health, Diponegoro University, 2012)
Background : Brebes as the largest users of pesticides (insecticide and fungicide) in Indonesia, have potential for the occurrence of pesticide poisoning which will give effect on health. Impacts of pesticide exposure with the incidence of anemia using indicators arsenic (As) in urine has not been known. This research aimed to identify association between pesticide exposure with the level of arsenic (As) in urine and incidence of anemia. Methods : this research was an observational research using a cross sectional design, with 32 samples farmer were taken by purposive sampling. Data levels of arsenic in urine in a test using spectrophotometry, while the haemoglobin concentration measured by Hemocue Hb201+, and for other data obtained by interview. Data analysis performed using Kendall-tau test (α = 0.05). Result : study showed level of arsenic (As) still below threshold limit value (NAB=<35 µg/l), the highest = 14.45 µg/l, the lowest = 1.40 µg/l, mean= 5.1137 µg/l and SD=3.271. While hemoglobin concentration with the results of five respondents (+) anemia, the highest=16.8 gr%, the lowest=11.3 gr%, mean= 14.159 gr% and SD=1.069. Statistical test results showed there was no significant association between doses of pesticides (p-value: 0.232), combinations of pesticides (p-value: 0.532), working hour/day (p-value: 0.797), duration of working (p-value: 0.515) and intensity of spraying (p-value: 0.834) with the level of arsenic (As) in urine and incidence of anemia (p-value: 0.152). T-test results showed average levels of arsenic (As) tend to be higher in respondents with duration of working (> 3 years) and working hour/day (≥ 3 hours/day) exposed to pesticides. Conclusion : The small sample size and indication of long term exposure is a potential factor in strengthening the conclusion there was no significant association between pesticides exposure, level of arsenic (As) in urine and incidence of anemia. Key words : Anemia, Arsenic, Pesticides Exposure